Nære relationers indvirkning på livsmodet - Delmar, Charlotte (Nordisk tidsskrift for helseforskning, 2019)
The impact of close relations on life courageThe purpose of this essay is to describe how close relations have impact on sick person’s life courage. Life courage is an existential life phenomenon. The life phenomena life courage and joy of life are in this article the key phenomena to be focused on. The article describes both differences and similarities between relational-ethical and existential life phenomena, which can promote but also restrict life. Moreover, some of the important differences between needs and life phenomena are also brought forward. The argumentation is based on empirical research examples of how close relations can contribute to creating life conducive or life restrictions for the ill and suffering person. It is in the interaction with others and through the importance of close relations that life courage possibilities arise. The article shows relational experiences from chronically ill persons, persons with a life-threatening disease and dying persons.
Keywords: life courage; joy of life; needs; close relations; livsmod; livsglæde; behov; nære relasjoner